2017
DOI: 10.2147/ndt.s134340
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of antipsychotics in the treatment of schizophrenia: a network meta-analysis in a Japanese population

Abstract: BackgroundThe relative efficacy and tolerability of antipsychotics for schizophrenia are considerably well studied. This study aimed to examine whether previous findings could be replicated in a genetically distinct and homogenous group (ie, Japanese patients with schizophrenia) and whether previous findings could be extended to a broader range of antipsychotics with previously unclear relative efficacy and tolerability.MethodsBayesian network meta-analysis was performed in which randomized trials comparing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Blonanserin produced fewer cases of faintness/dizziness, psychomotor retardation, and diarrhea than did haloperidol. In our recent network meta-analysis evaluating the comparative efficacy and safety of antipsychotics for the treatment of Japanese patients with schizophrenia [6], blonanserin was the first-ranked antipsychotic for the lowest risk of weight change and was the second-lowest ranked antipsychotic for the risk of drowsiness, sedation, and somnolence. These findings are consistent with the results of previous meta-analyzes in which blonanserin exhibited a lower risk of weight gain than did risperidone and lower risk of dizziness than did haloperidol [3,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blonanserin produced fewer cases of faintness/dizziness, psychomotor retardation, and diarrhea than did haloperidol. In our recent network meta-analysis evaluating the comparative efficacy and safety of antipsychotics for the treatment of Japanese patients with schizophrenia [6], blonanserin was the first-ranked antipsychotic for the lowest risk of weight change and was the second-lowest ranked antipsychotic for the risk of drowsiness, sedation, and somnolence. These findings are consistent with the results of previous meta-analyzes in which blonanserin exhibited a lower risk of weight gain than did risperidone and lower risk of dizziness than did haloperidol [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…To identify relevant RCTs, an electronic search was conducted using Embase, Medline/PubMed, the Cochrane Library, the U.S. National Institutes of Health Clinical Trials Registry (http://www.clinicaltrials.gov), and the University Hospital Medical Information Network Clinical Trials Registry (UMIN-CTR; http://www.umin.ac.jp/ctr/ index.htm); the last search was performed on September 26, 2017, using the following search terms: "blonanserin" AND "schizophrenia" AND "random," "randomly," OR "randomized." Additional eligible RCTs were also sought through a manual search of reference lists from relevant articles and reviews [3,5,6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…But when switching with the aim of enhancing therapeutic efficacy (Dold and Leucht, 2014), which antipsychotic medication should be chosen? Meta-analyses of RCTs reveal only modest differences in efficacy between the available non-clozapine antipsychotic medications and the clinical significance of any such small efficacy advantages is uncertain (Kishi et al, 2017a; Leucht et al, 2013).…”
Section: Maintaining Responsementioning
confidence: 99%
“…However, blonanserin induced less BW gain compared with risperidone. Furthermore, a recent network meta-analysis indicated that blonanserin was the most BW-neutral antipsychotic, with even less effect on BW than aripiprazole 33). As positive effects can be achieved when switching treatment from metabolically disruptive antipsychotics to more BW-neutral antipsychotics,27) the results of the present study suggest other benefits of switching to blonanserin from other antipsychotics that have a high to moderate risk of inducing metabolic abnormalities, including olanzapine, quetiapine, and risperidone.…”
Section: Discussionmentioning
confidence: 50%